PENGARUH KOMPENSASI, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA BALAI PEMASYARAKATAN KELAS I MAKASSAR - Ardyansyah Rahmat; Abd. Gaffar; Syahrir S (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of compensation, work motivation, and work environment on employee productivity at the Class I Makassar Correctional Center. This research uses a quantitative approach with an explanatory design. The research population consisted of 121 employees. Data were collected using a five-point Likert scale questionnaire and analyzed using SPSS 25. The results of the study indicate that compensation has a positive and significant effect on work productivity, while work motivation has no significant effect and the work environment has no significant effect. Simultaneously, the three variables have a significant influence on work productivity. The main finding shows that compensation is the only independent variable that is proven to be partially significant.